Síntese e análise estrutural de complexos de urânio (VI) coordenados aos ligantes hidrocloreto de piridoxina, 4-fenil-semicarbazida e a 2-(2´-hidroxifenil) benzoxazola. - Back, Davi Fernando (2004)
The synthesis and structural analysis of three new coordination compounds containing uranium metal are described in this dissertation. These compositions were synthesized with a mimetic ligand to a biological structure, well with a ligand of biological function described in the literature. The compound (UO2)(Pyridoxine Hydrocloride)2(H2O) was synthesized by the reaction of pyridoxine, uranyl nitrate and triethylamine in acetonitrile. After 3 weeks darkness orange crystals were obtained. It was verified that these crystals belonged to the triclinic system, space group P¯1 , the constants of cell are: a = 7.5298(5) Å, b = 8.9828(7) Å, c =16.7710(12) Å, α = 75.2930(10) Å, β = 89.249(2) Å, γ = 80.5320(10) Å. The X-ray diffraction demonstrates that in this complex the uranium atom is in the form of a uranyl moiety (UO2) and coordinates with two molecules of the bidentate ligand pyridoxine and a water molecule, to form a pentagonal bipyramidal coordenation geometry. The compound [(UO2)(4-Phenil-Semicarbazid)3](NO3)2 was obtained by the reaction of the uranyl nitrate and 4-phenil-semicarbazid in acetonitrile. Yellows crystals of cubic habit were obtained after two days. The structural analysis revealed that these crystals belong to the monoclinic system, space group P21/c. The cell constants found were a = 12.618(3) Å, b = 16.810(17) Å, c = 15.189(2), β = 93.23(2)°. The coordination geometry found for the uranium atom is hexagonal bipyramidal. In addition to the two uranyl oxigen atoms bound to the metal (UO2), three molecules of the bidentate ligand 4- phenil-semicarbazid coordenate to the uranium center. The compound [(UO2) 2-(2´-Hydroxyphenyl) Benzoxazole)2(MeOH)] was obtained by the reaction of 2-(2´-hydroxyphenil) benzoxazole and uranyl nitrate in methanol. Red and prismatic crystals formed. The crystalline system of this compound is monoclinic in the space group P21/c, the ceel constants are: a = 13.477(3) Å, b = 19.344(4) Å, c = 9.3029(19) Å, β = 92.306(5) Å. The pentagonal bipyramidal coordination geometry of this compound is make up whit two molecules of the bidentate ligand and one molecule of methanol coordenating to the uranyl grup (UO2).